TOURIST CLUSTER AS AN INNOVATIVE FORM OF TOURISM DEVELOPMENT IN UKRAINE - PEREPELIUKOVA, OLENA (Herald of Khmelnytskyi National University. Economic sciences, 2021)
The article examines the peculiarities of the formation and functioning of tourist clusters in Ukraine. The peculiarities of the functioning of such clusters during the pandemic were determined. It has been established that this form of tourism business development is currently effective, as it contributes to increasing the competitiveness of enterprises and the region on the foreign market. The formation of tourist clusters allows companies operating in different sectors of the economy to unite, while their joint activities contribute to the development of the tourism business. The effectiveness of the development of this form of cooperation is explained by the fact that such entities operate in a homogeneous segment, but each occupies its own niche. It has been proven that the peculiarity of the formation of tourism clusters is that the enterprises in the cluster have a higher level of interaction, changing their form from target associations of enterprises to powerful, well-structured commercial entities. It has been proven that cluster models of tourism organization are distinguished by the imperfection of centralized influence, the appropriate observance of conditions of equality, the creation of conditions for the growth of market competition.It was established that the development of the tourist cluster is carried out on the basis of the involvement of large commercial and industrial structures, the involvement of regional and national authorities.Associations of enterprises form an appropriate tourism system, which includes the assets of tourism product production of enterprises of various sectors of the economy, which are united in one tourism cluster. For the development of the tourist business and the attraction of investment resources, it is advisable to form the appropriate tourist-type economic zones, which will contribute to the increase of entrepreneurial initiatives, the use of tourist resources, and the improvement of the status and economic attractiveness of the region.It has been proven that enterprises that are united in tourism clusters within the region have the opportunity to more effectively use the investment capacity of the region, to cooperate with regional authorities due to participation in regional investment and innovation projects.
Keywords: tourism cluster; innovation; economy; efficiency; pandemic